Estimating Security Betas Using Prior Information Based on Firm Fundamentals - Cosemans, Mathijs; Frehen, Rik; Schotman, Peter C.; Bauer, Rob (Review of Financial Studies, 2016)
We propose a hybrid approach for estimating beta that shrinks rolling window estimates toward firm-specific priors motivated by economic theory. Our method yields superior forecasts of beta that have important practical implications. First, unlike standard rolling window betas, hybrid betas carry a significant price of risk in the cross-section even after controlling for characteristics. Second, the hybrid approach offers statistically and economically significant out-of-sample benefits for investors who use factor models to construct optimal portfolios. We show that the hybrid estimator outperforms existing estimators because shrinkage toward a fundamentals-based prior is effective in reducing measurement noise in extreme beta estimates. Received May 17, 2011; accepted October 7, 2015 by Editor Geert Bekaert.